PREDIKSI EROSI TANAH DI DAS (DAERAH ALIRAN SUNGAI) PANEKI KECAMATAN BIROMARU KABUPATEN SIGI - Kias, Muhamad Fadli; Ramlan, Ramlan; Zainuddin, Rahmat (AGROTEKBIS, 2016)
The aims of this study were to predict soil erosion and to determine erosion threat index occurred in the Paneki watershed, Pombewe village Biromaru district Sigi Regency, Central Sulawesi. This study contributed as a source of information for the development of land use management as well as conservation of soil and water. Furthermore, it was important to complete a number of soil physical properties. The method used in this study was descriptive explorative by conducting survey in the research site, followed by primary and secondary data collection. In this study, it was required slope class maps, soil maps and land use maps application using ArcGIS 10.0 for obtaining four (4) land units, namely land, secondary forest, mixed farms, fields and cocoa plantations. Results of this study indicated that the physical characteristics of soil in some land use vary greatly with slow to moderate permeability, soil texture dominated by sandy loam and loam fractions. Both bulk density and C-organic content were high. Prediction of soil erosion rate using the USLE (Universal Soil Loss Equation) formula indicated that erosion threat index occured in Paneki watershed was classified at low to moderate levels with the average number of total allowable erosion was 74.12 tons ha-1 yr-1.